REDESAIN SISTEM DAN PROSEDUR PENGGAJIAN PADA TRANSINDO XPRESS DI KABUPATEN JEMBER - Z, Achmad Syahfrudin; Prastika, Dea Safila; Probowulan, Diyah (Fakultas Ekonomi dan Bisnis, 2022)
There is no denying that information technology has become an extraordinary tool for businesses in this fourth industrial revolution era. Information systems will be more efficient and effective along with advances in information technology. It is important for a business to have a reliable payroll system as it is an integral part of the company's accounting system and will provide detailed and accurate data through established practices and documentation on the compensation provided to its employees. Staff members need to be managed effectively. For smooth business operations and fulfillment of organizational objectives, payroll system errors must be avoided at all costs.This research is focused on updating the payroll system design at Transindo Xpress which still uses a manual system for recording payroll and the payroll system used is still weak. So that the reporting experience is not timely and must be re-checked against recording employee salaries.